2017
DOI: 10.1371/journal.pone.0177994
|View full text |Cite
|
Sign up to set email alerts
|

A Rho-associated coiled-coil containing kinases (ROCK) inhibitor, Y-27632, enhances adhesion, viability and differentiation of human term placenta-derived trophoblasts in vitro

Abstract: Although human term placenta-derived primary cytotrophoblasts (pCTBs) represent a good human syncytiotrophoblast (STB) model, in vitro culture of pCTBs is not always easily accomplished. Y-27632, a specific inhibitor of Rho-associated coiled-coil containing kinases (ROCK), reportedly prevented apoptosis and improved cell-to-substrate adhesion and culture stability of dissociated cultured human embryonic stem cells and human corneal endothelial cells. The Rho kinase pathway regulates various kinds of cell behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…TWIST1 39 was not expressed in BeWo cells at any timepoint, regardless of forskolin treatment, yet was consistently expressed in human placental cells, but with no marked up- or down-regulation during syncytialization. ROCK1 and RAC1 40 were expressed at similar levels across all time points and treatments. Both LAT1 and 4F2hc 41 were upregulated 3–4 fold in forskolin-treated BeWo cells at 72 hours.…”
Section: Discussionmentioning
confidence: 89%
“…TWIST1 39 was not expressed in BeWo cells at any timepoint, regardless of forskolin treatment, yet was consistently expressed in human placental cells, but with no marked up- or down-regulation during syncytialization. ROCK1 and RAC1 40 were expressed at similar levels across all time points and treatments. Both LAT1 and 4F2hc 41 were upregulated 3–4 fold in forskolin-treated BeWo cells at 72 hours.…”
Section: Discussionmentioning
confidence: 89%
“…[51][52][53][54] It has been recently reported that one cellular response to hypoxia-ischemia is mRNA stabilization and promotion of translation through m 6 A modification of the transcription factors JUN and MYC, demonstrating that mRNA degradation is not the only effect of m 6 A. In the future, using techniques such as first-stage cell culture of patient-derived villi, 56 we intend to investigate details of the relationships between various stresses and m 6 A levels especially at the 5′-UTR to further clarify the significance of m 6 A in placental mRNAs. Additionally, JUN is among the list of 5′-UTR DMGs among these categories (Supplemental Data).…”
Section: Discussionmentioning
confidence: 99%
“…ROCK inhibition is known to facilitate the growth and survival of human embryonic stem cells by inhibiting anoikis. ROCK inhibitors are now part of standard stem cell culture protocols [ 51 , 52 ]. Our results show that Y27632 can also increase the in vitro viability of MDA-MB-231 spheroids ( Supplementary Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%